2011
DOI: 10.6028/jres.116.016
|View full text |Cite
|
Sign up to set email alerts
|

Improved first-principles calculation of the third virial coefficient of helium

Abstract: We employ state-of-the-art pair and three-body potentials with path-integral Monte Carlo (PIMC) methods to calculate the third density virial coefficient C(T) for helium. The uncertainties are much smaller than those of the best experimental results, and approximately one-fourth the uncertainty of our previous work. We have extended our results in temperature down to 2.6 K, incorporating the effect of spin statistics that become important below approximately 7 K. Results are given for both the 3He and 4He isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 24 publications
8
104
1
1
Order By: Relevance
“…where from theory [32]. The opportunity of the latter assumption relies on the observation that when A 2 is left as a free parameter in fitting (18), it is found to be not significantly different from zero: is based on the analysis of a significantly restricted dataset which excludes several modes and all the low-pressure data below 170 kPa.…”
Section: Isotherm Analysis and Final Acoustic Resultsmentioning
confidence: 99%
“…where from theory [32]. The opportunity of the latter assumption relies on the observation that when A 2 is left as a free parameter in fitting (18), it is found to be not significantly different from zero: is based on the analysis of a significantly restricted dataset which excludes several modes and all the low-pressure data below 170 kPa.…”
Section: Isotherm Analysis and Final Acoustic Resultsmentioning
confidence: 99%
“…Semi-classical virial coefficients up to fifth order have been computed for helium-4 by Shaul et al [15], and showed that first-principles properties could be evaluated with precision and accuracy that exceeds experiment. Garberoglio and Harvey [9,16,17] reported fully quantum second and third virial coefficients for helium-3 and helium-4 including exchange effects where needed, for temperatures as low as 2.6 K. Shaul et al [18] reported fully quantum virial coefficients of helium-4 (but without exchange) up to fourth order for temperatures of T = 2.6-1000 K.…”
Section: Tr Ementioning
confidence: 99%
“…(15) to a quantity that is dependent on both P and h as in Eq. (17). The inter-molecular potential experienced by the beads of the ring changes from being classical to semi-classical (dependent on P and h).…”
Section: Thermal Density Matrix and Pimcmentioning
confidence: 99%
“…Среди имеющихся способов расчета в настоящее время наиболее перспективным представляется использование интегралов по траек-ториям Фейнмана и метода Монте-Карло (см. [48] и цитированную там литературу). Не менее важным является также развитие методов вычисления эффективного по-тенциала взаимодействия исходных атомов (15), где, на наш взгляд, наибольший интерес представляет ТФМП [29]- [31].…”
unclassified